2008
DOI: 10.1007/s11481-008-9124-4
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Infections in the Intensive Care Unit Should Clinicians and Patients be Concerned?

Abstract: There is a large body of experimental evidence in research animals and in vitro models that opioids suppress the immune system. If this effect occurs in acute human disease, then patients cared for in Intensive Care Units (ICUs) would be a particularly vulnerable population. ICU patients have the most severe forms of acute infection, have the greatest risk of acquiring new infections in the hospital, and are exposed to high doses of opioids for long periods of time. We review the epidemiology of ICU infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 104 publications
0
8
0
1
Order By: Relevance
“…Indeed, available evidence indicates that opioids have immunosuppressive effects and are capable of increasing mortality in animal models of infection [27,56]. Additionally, fentanyl may contribute to delirium [6].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, available evidence indicates that opioids have immunosuppressive effects and are capable of increasing mortality in animal models of infection [27,56]. Additionally, fentanyl may contribute to delirium [6].…”
Section: Discussionmentioning
confidence: 99%
“…The Society of Critical Care Medicine advocates the use of morphine as the drug of choice for pain management in mechanically ventilated patients [3]. A systematic review of 43 studies analyzing the use of opioids in patients in the intensive care unit concluded that the median morphine dose was 0.7 mg/kg/day or approximately 49mg/day in a 70kg patient [4]. However, opioids are known to cause respiratory depression and subsequent cardiopulmonary arrests.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 They are potent analgesics, have few clinically apparent adverse effects on other organ systems, and have consistent pharmacokinetics. 4 Opioids are naturally occurring alkaloids, related synthetic/semisynthetic compounds, and endogenous opioid peptides (enkephalins, endorphins, and dynorphins). 5 The exact physiologic function of endogenous opioids includes modulation of stress-induced analgesia and neurotransmitter, neuromodulator, and neurohormonal activity.…”
Section: Introductionmentioning
confidence: 99%